Elucidation Of The Role Of Long Noncoding Rna Kcnma1-As2 In Colorectal Cancer - Miao, Xinzhi (2024)
The aberrant expression of long noncoding RNAs (lncRNAs) is frequently documented in colorectal cancer (CRC). This anomalous expression is associated with tumourigenesis by promoting detrimental biological behaviours in tumour cells, including proliferation, apoptosis, cell cycle progression, and migration. A growing body of evidence suggests that lncRNAs play pivotal roles in tumour regulation at both molecular and cellular dimensions. Some lncRNAs function as oncogenes and exhibit increased expression, while others act as tumour suppressors and show reduced levels in cancerous tissues. Furthermore, lncRNAs can regulate processes by targeting miRNAs, serving as competing endogenous RNAs. This study seeks to discover novel lncRNA entities and comprehensively examine and validate their roles and underlying molecular mechanisms in CRC. Tissue samples, both tumourous and non-tumourous, from three CRC patients were submitted for sequencing. The sequencing results indicated 148 up-regulated and 146 down-regulated lncRNAs. Following expression validation in samples from ten patients and four CRC cell lines, LINC00668 was identified as an up-regulated lncRNA. An siRNA knockdown was performed on LINC00668 to assess if altering its impact on CRC cell functions. The MTT assay was used to measure cell proliferation. The Annexin-V/PI apoptosis assay was performed to determine cell apoptosis. To analyse the cell cycle, a cell cycle assay was conducted, and a wound healing assay was utilised to evaluate cell migration. However, no significant effects on cell proliferation or apoptosis were observed post-knockdown of LINC00668, leading to its exclusion from subsequent research.